React: Facebook's Functional Turn on Writing JavaScript. - Hunt, Pete; O'Shannessy, Paul; Smith, Dave; Coatta, Terry (Communications of the ACM, 2016)
An interview with former social media firm Facebook's React core team member Pete Hunt and Facebook engineer Paul O'Shannessy is presented in which they discuss Facebook's decision to open source its React library in order to build user interface components, which are constructed from JavaScript objects and away from the Document Object Model (DOM).